2017
DOI: 10.1088/1752-7163/aa6368
|View full text |Cite
|
Sign up to set email alerts
|

Oral or nasal breathing? Real-time effects of switching sampling route onto exhaled VOC concentrations

Abstract: There is a need for standardisation in sampling and analysis of breath volatile organic compounds (VOCs) in order to minimise ubiquitous confounding effects. Physiological factors may mask concentration changes induced by pathophysiological effects. In humans, unconscious switching of oral and nasal breathing can occur during breath sampling, which may affect VOC patterns. Here, we investigated exhaled VOC concentrations in real-time while switching breathing routes. Breath from 15 healthy volunteers was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 39 publications
1
77
0
Order By: Relevance
“…Breath hydrogen sulphide is sourced from oral bacterial emissions and AMS is known to originate from food constituent e.g. garlic, onions etc 59 . Here, hydrogen sulphide exhalation did not change whereas AMS showed similar tendencies as DMS in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Breath hydrogen sulphide is sourced from oral bacterial emissions and AMS is known to originate from food constituent e.g. garlic, onions etc 59 . Here, hydrogen sulphide exhalation did not change whereas AMS showed similar tendencies as DMS in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…[29][30][31] An air sampling method was selected to collect inhaled and exhaled air for each subject. [29][30][31] An air sampling method was selected to collect inhaled and exhaled air for each subject.…”
Section: Me Thodsmentioning
confidence: 99%
“…As the breath modality such as oral or nasal, body position, and breath holding may significantly effect on exhaled concentrations, the breathing sampling process should be normalized and strictly monitored. [29][30][31] An air sampling method was selected to collect inhaled and exhaled air for each subject. 12 The apparatus of collecting exhaled air was composed of a disposable blow nozzle, a spherical condenser and a Tedlar gas sampling bag (Alllabware Scientific, 5 L).…”
Section: Me Thodsmentioning
confidence: 99%